The gay and lesbian emancipation policy of the city of Amsterdam - Nijboer, Jeannette; Veeger, Margriet (Amsterdam : Communications Department of the city of Amsterdam, 1998)
Fonds Suzan Daniel (FSD)
Engels
Brochure